Observation and analysis of near-surface pore-pressure measurements in clay-shales slopes - Berti, Matteo; Simoni, Alessandro (Hydrological processes, 2012)
Clay‐shales largely outcrop in the Northern Apennines of Italy, where they are associated with frequent and widespread landslide activity. The paper presents the results of monitoring activities carried out in two field‐sites and focused on the hydrology of clay‐shales prone to landsliding. In the monitored slopes, the water table is close to the ground surface throughout the year, with seasonal fluctuations of tens of centimetres to a couple of metres. Shallow weathered soils, or clay cover, and unaltered material exhibit a much different behaviour. Although responses to single rainfalls are clearly identifiable as pressure pulses in the clay cover, they are never observed in the underlying parental clay‐shales where downward gradients indicate recharge and only long‐term seasonal fluctuations are recorded. Short‐term variations of pressure head in the clay cover are ruled by downward propagation of a pressure wave in saturated conditions. More than 400 pore‐pressure responses collected in the two sites are analysed in terms of lag time, rate and amount of pressure increase and timing of pressure peaking. It emerges that the linear diffusion theory can satisfactorily explain the observed behaviour. In deeper unaltered material, the barometric effect influences the measures similarly to what is observed in confined aquifers. After its removal, the corrected data exhibit regular seasonal fluctuations which are used to estimate the diffusivity of the material based on phase‐lag and attenuation of the downward propagating long‐term periodic pulse. Copyright © 2011 John Wiley & Sons, Ltd.